Psikologi dan Pendidikan Dalam Perspektif Al Qur’an: Studi Al Qur’an Tematik - Rajib Dafa Al Fikri; Muhammad Alif (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Psychology and education are two fields of knowledge that play a crucial role in understanding and optimizing human abilities as a whole. Various current educational issues, such as the crisis of character, declining moral values, and increasing psychological problems among students, reflect the limitations of educational methods that overly focus on cognitive aspects. The Qur'an, as the primary source of Islamic teachings, provides a comprehensive perspective on the nature of human beings and the processes related to their education, including the psychological dimensions inherent in individuals. This study aims to analyze the concepts of psychology and education from the perspective of the Qur'an using a thematic exegesis (maudhu‘i) approach. The chosen method is qualitative and based on a literature review with the Qur'an as the main data source, supported by references from tafsir books and Islamic educational psychology literature. The findings of the study indicate that the concepts of nafs, qalb, ‘aql, and fitrah are interconnected in shaping individual personality and behavior, and serve as the foundation for Islamic education that emphasizes balance between intellectual, emotional, moral, and spiritual aspects. Therefore, Qur'anic psychology has the potential to become an alternative foundation in addressing the challenges of contemporary education, particularly in character development and student mental well-being.Keywords: Qur'anic Psychology, Islamic Education, Thematic Exegesis   Abstrak Psikologi dan pendidikan adalah dua bidang ilmu yang sangat berpengaruh dalam memahami serta mengoptimalkan kemampuan manusia secara keseluruhan. Berbagai isu pendidikan saat ini, seperti krisis karakter, penurunan nilai moral, dan meningkatnya masalah psikologis di kalangan siswa, mencerminkan batasan dari metode pendidikan yang terlalu fokus pada aspek kognisi. Al-Qur’an sebagai sumber utama ajaran Islam memberikan perspektif menyeluruh tentang hakikat manusia dan proses yang terkait dengan pendidikannya, termasuk dimensi psikologis yang melekat pada individu. Penelitian ini bertujuan untuk menganalisis konsep psikologi dan pendidikan melalui sudut pandang Al-Qur’an dengan menggunakan pendekatan tafsir tematik (maudhu‘i). Metode yang dipilih adalah kualitatif dan didasarkan pada kajian literatur dengan Al-Qur’an sebagai sumber data utama serta referensi dari kitab tafsir dan literatur psikologi pendidikan Islam sebagai penunjang. Temuan dari kajian menunjukkan bahwa konsep nafs, qalb, ‘aql, dan fitrah saling terhubung dalam membangun kepribadian dan perilaku individu, serta menjadi landasan pendidikan Islam yang menekankan keseimbangan antara aspek intelektual, emosional, moral, dan spiritual. Oleh karena itu, psikologi Qur'ani berpotensi menjadi dasar alternatif dalam menghadapi tantangan pendidikan masa kini, terutama dalam pengembangan karakter dan kesejahteraan mental siswa. Kata kunci: Psikologi Qur’ani, Pendidikan Islam, Tafsir Tematik